Analyzing Audit Delay in the Property and Real Estate Sector: The Role of Company Size as a Control Factor - Ilham, Ilham (PT Bone Jaya Kreatif, 2024)
Based on data from the Indonesia Stock Exchange (IDX), the real estate and property sector recorded the highest number of cases where companies failed to submit audited financial statements during the 2020-2021 period. Therefore, this study aims to identify the factors that influence audit delays in real estate and property companies in Indonesia. The study utilizes agency theory as the theoretical framework. A quantitative approach was employed, using secondary data. The research population consists of real estate and property companies listed on the IDX, with 69 companies selected as the sample through purposive sampling. The independent variables include audit opinion, size of the Public Accounting Firm (KAP), audit tenure, and auditor turnover, while the dependent variable is audit delay, with company size as the control variable. Multiple linear regression was used as the analysis method in this study. The findings indicate that audit opinion affects audit delay, whereas the size of the Public Accounting Firm (KAP), audit tenure, and auditor turnover have no significant impact. Companies are encouraged to be more vigilant regarding factors that could lead to longer audit delays, including avoiding material misstatements in financial reports that could affect the audit opinion received